1999
DOI: 10.2307/1447386
|View full text |Cite
|
Sign up to set email alerts
|

Age, Growth, and Reproduction of the Pelagic Thresher Shark, Alopias pelagicus in the Northwestern Pacific

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. American Society of Ichthyologists and Herpetologists (ASIH)is collaborating with JSTOR to digitize, preserve and extend access to Copeia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
136
4
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(150 citation statements)
references
References 7 publications
8
136
4
2
Order By: Relevance
“…missing the head and tail) pelagic threshers and for the largest bigeye thresher (which was not weighed), morphometric parameters were estimated using established fork length (FL) to total length (TL) and TL vs body mass regressions. Pelagic thresher alternate-length (insertion of first dorsal to insertion of second dorsal) was converted to TL using data from the California Drift Gillnet Fishery database (D. Holts, National Marine Fisheries Service, unpublished), and TL-body mass relationships were determined using regressions from Liu et al (1999). The body mass of the A. superciliosus specimen was determined using data from Kohler et al (1995).…”
Section: Body Sizementioning
confidence: 99%
See 1 more Smart Citation
“…missing the head and tail) pelagic threshers and for the largest bigeye thresher (which was not weighed), morphometric parameters were estimated using established fork length (FL) to total length (TL) and TL vs body mass regressions. Pelagic thresher alternate-length (insertion of first dorsal to insertion of second dorsal) was converted to TL using data from the California Drift Gillnet Fishery database (D. Holts, National Marine Fisheries Service, unpublished), and TL-body mass relationships were determined using regressions from Liu et al (1999). The body mass of the A. superciliosus specimen was determined using data from Kohler et al (1995).…”
Section: Body Sizementioning
confidence: 99%
“…While all three thresher species, at times, occupy similar depths and habitats (Hanan et al, 1993); latitudinal and depthdistribution data suggest that A. vulpinus, with its warm RM, and A. superciliosus, which is probably a cranial endotherm (Weng and Block, 2004), inhabit cooler waters than A. pelagicus, a species predominantly found in tropical and subtropical waters (Compagno, 1998;Liu et al, 1999). A. vulpinus has been shown to have the greatest overall latitudinal distribution, ranging in the eastern Pacific from 58°N to 55°S (Compagno, 2001).…”
Section: Regional Endothermy and Thresher Shark Natural Historymentioning
confidence: 99%
“…Males reach adult at size about 240-250 cm and females at 260-285 cm (White et al, 2006;White, 2007). Liu et al (1999) reported that the total length at maturity was 282-292 cm for females and 267-276 cm for males. Based on the results of this study, it can be concluded that the majority A. pelagicus caught from the Indian Ocean on 2002-2007 are commonly as adult stage (mature non reproductive or mature sexually).…”
Section: Discussionmentioning
confidence: 99%
“…) showing late sexual maturity (8.0-9.2 years for females and 7.0 -8.0 years for males) and usually producing about two embryos per litter (Liu et al, 1999).…”
mentioning
confidence: 99%